First record of Scleroderma bovista (Boletales, Sclerodermataceae) for Colombia - Pinzón Osorio, César Augusto (2018)
Scleroderma bovista is described and illustrated for the first time in Colombia. Scleroderma bovista is a gasteroid fungi found on the campus of the Universidad Pedagógica Nacional (Bogotá), department of Cundinamarca. Information on distribution, ecology and growth substrate is provided. Thus, the genus Scleroderma is represented in the country by four species: S. albidum, S. areolatum, S. citrinum y S. bovista.